Dehydrogenase activity and zinc equivalent parameters as indicators for potential toxic elements remediation in polluted soil ecosystem. Issue 4 (2nd October 2019) - Mansour, H.; Saber, M.; Awad, F.; Zaghloul, A.
Abstract: As far as potential toxic elements (PTEs) have definite numerous adverse impacts on soil ecosystems; there is an urgent need for proper indicators to monitor their remediation process. Certainly, monitoring soil remediation process would enable assessing the efficiency of varied remediation techniques. Remediation of soil ecosystem pollution using protocols of chemical remediative amendments, i.e., (elemental sulfur, rock phosphate, bentonite and kaolinite) and biological remediative amendments, i.e., ( Thiobacillus thiooxidans, Thiobacillus ferrooxidans, phosphate dissolving bacteria and Pseudomonas fluorescens ) were evaluated under field conditions in a heavy metals contaminated soil ecosystem cultivated with the hyper accumulator turnip. Results showed a significant decrease in the hazards of PTEs in the studied soil ecosystem represented by decreasing Zinc equivalent (ZE) values from 854.5 ppm in the uncultivated control soil to 498.3 ppm in the cultivated control soil. Application of the treatment (T7 ), was the best treatment applied, this treatment decreased ZE value to 104.2 ppm. Significant negative correlations were detected between dehydrogenase activity (DHA) as a biological indicator for the whole microbial activity in the soil ecosystem and Zn Equivalent (ZE) as a chemical indicator parameter in both treated and untreated soils. The results of this work imply that the used treatments significantly returned the contaminated soil to a healthy soil.